2019
DOI: 10.7324/japs.2019.90317
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and pharmacological aspects of Tephrosia genus: A brief review

Abstract: Tephrosia, the plant genus belongs to the family Fabaceae. It belongs to the major group of angiosperms (flowering plants) that comprises more than 350 species which is widely distributed in the regions of tropical and subtropical countries of the world. Since the herbal medicine is in demand due to its fewer associated side effects, the genus Tephrosia is extensively used for the treatment of large number of diseases in traditional medicines. The main aim of this review is to summarize and document the phytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…(Fabaceae) mainly inhabit tropical and subtropical regions with over 30 species occurring in Kenya . Many of the species have been used ethnomedicinally to alleviate diverse illnesses. , Phytochemical investigations of some of these plants by our research group have led to the isolation of a chalcone, rotenoids, flavanonols, and flavones that are biologically active. Also, the genus Tephrosia is reported to elaborate other bioactive flavonoids such as flavanones, isoflavones, and pterocarpans. , Some of these flavonoids also exhibit anti-inflammatory properties.…”
mentioning
confidence: 99%
“…(Fabaceae) mainly inhabit tropical and subtropical regions with over 30 species occurring in Kenya . Many of the species have been used ethnomedicinally to alleviate diverse illnesses. , Phytochemical investigations of some of these plants by our research group have led to the isolation of a chalcone, rotenoids, flavanonols, and flavones that are biologically active. Also, the genus Tephrosia is reported to elaborate other bioactive flavonoids such as flavanones, isoflavones, and pterocarpans. , Some of these flavonoids also exhibit anti-inflammatory properties.…”
mentioning
confidence: 99%
“…Also, this study on phytochemical screening revealed the absence of alkaloids and anthraquinones suggesting that these medicinal properties of Tephrosia vogelii found particularly in Tanzania may be branded mainly by tannins, steroids, terpenes, flavonoids and glycosides. On the other hand, the chemical nature of the phytochemicals analysed from this medicinal plant clearly coincides with the antimicrobial activities and ectoparasitic activities reported in the previous studies (Alamgir, 2017;Arif et al, 2011;Badri et al, 2017;Kenechukwu et al, 2012;Irawan et al, 2018;Makoshi & Arowolo, 2011;Mbunde et al, 2016;Mlozi et al, 2020;Murtaza et al, 2015;Nneka & Jude, 2012;Okpogba et al, 2019;Omodamiro & Amechi, 2013;Pietta, 2000;Priya et al, 2014;Ramawat & Mérillon, 2013;Sahu et al, 2014;Samuel et al, 2019;Sasidharan et al, 2011;Singh et al, 2017;Swamy et al, 2015;Trakranrungsie, 2011).…”
Section: Phytochemical Investigationsupporting
confidence: 86%
“…On the other hand, pharmacological studies of Swamy and colleagues (2015) pointed-out the usefulness of Tephrosia vogelii as a medicinal plant for management of bacterial diseases (Inalegwu & Sodipo, 2015;Swamy et al, 2015). The biological assay of ether-ethanolic extracts of Tephrosia vogelii seeds showed that the extracts exhibit anti-oxidants and free scavenging properties, and hence indicated the presence of flavonoids which have been reported to be responsible for such antioxidant and free radical scavenging properties (Samuel et al, 2019). Other studies reported that the methanolic extracts of Tephrosia vogelii also exhibited purgative activities after being subjected to the rabbit (Samuel et al, 2019).…”
Section: Pharmacological Features Of Tephrosia Vogeliimentioning
confidence: 99%
See 1 more Smart Citation
“…Extract of TP possess free radical scavenging activity and antioxidant properties due to presence of various phytochemicals like alkaloids, amino acids, glycosides, sterols, rotenoids, isoflavones, flavanones, flavonoids, chalcones, flavanols, flavones, saponins, reducing sugars, terpenes and tannis. [9][10][11] Due to presence of these phytochemicals, it has a peculiar property of curing all types of wounds. Hence, it is known as "Sarwa wranvishapaka".…”
Section: Introductionmentioning
confidence: 99%